Manajemen Olahraga di Klub Renang Tirta Kusuma Kabupaten Pati Tahun 2021 (Universitas Negeri Semarang, 2021)
ABSTRACT Rizki Burhana Robbi. 2021. Sports Management at the Tirta Kusuma Swimming Club, Pati Regency in 2021. Thesis, Department of Physical Education, Health and Recreation, Faculty of Sports Science, State University of Semarang, Advisor Dr. Tommy Soenyoto, S. Pd., M.d. Keywords: Management, Swimming Sport. Management is process-oriented, which means that management requires human resources, knowledge and skills so that activities are more effective or can result in actions to achieve success. The focus in this problem is how the management at the Tirta Kusuma swimming club, Pati Regency, from planning, organizing, implementing and supervising. The purpose of this study was to determine and analyze the existing management at the Tirta Kusuma swimming club, Pati Regency from planning, organizing, actuating and supervising. This research approach uses qualitative research. The method used is descriptive method. Research instruments include observation, interviews and documentation. The location of the research was carried out at the Joyo Kusumo Pati swimming pool and at the PRSI Regency Government Secretariat Pati Regency. while the targets in this study were club leaders, coaches, athletes, managers and head of the PRSI district Pati. The results showed that the Tirta Kusuma swimming club in Pati Regency had a good plan. The organizing management function already has a systematic management structure that works according to their respective duties. The implementation management function is good in terms of coaching and training programs. The management function of technical supervision and security at the Tirta Kusuma Swimming Club is carried out well by the administrators, coaches, athletes, managers and the PRSI Regency. Based on the results of the data obtained, it can be concluded that the management of the Tirta Kusuma swimming club has been running in accordance with the management function. The suggestion that the author can convey is that the Tirta Kusuma swimming club management should be able to find alternative training sites with a length of 50m to support maximum training. The manager of the Tirta Kusuma swimming club can improve the training system, by dividing each coach into one group. This makes it easier for coaches to focus more on monitoring the progress of their athletes, and makes it easier for athletes to understand the training program provided by the coach.